Program GEMBIRA: Intervensi Edukatif Berbasis Komunitas untuk Meningkatkan Perilaku Hidup Bersih dan Sehat pada Anak Usia Sekolah di Desa Sukorambi, Jember: The GEMBIRA Program: A Community-Based Educational Intervention to Promote Clean and Healthy Behavior Among School-Aged Children in Sukorambi, Jember - Idfiana Hilmi; Riza Rohmatul Maulidia; Putra Adinata; Tantut Susanto; Yuyus Febsyna (Poltekkes Kemenkes Yogyakarta, 2025)
Diarrheal diseases among school-aged children in rural areas remain a public health challenge, driven by low Clean and Healthy Behaviour (PHBS) practices and limited sanitation facilities. This community service project aimed to implement and evaluate the effectiveness of the GEMBIRA (Gerakan Membiasakan Bersih dan Rajin pada Anak) program in improving health knowledge, attitudes, and PHBS skills among elementary school children in RW 08 Krajan Hamlet, Sukorambi Village, Jember Regency. The activity utilized a Community-Based Behavioral Intervention approach, integrating promotive education, participatory learning, and community empowerment. The intervention was conducted between August and September 2025 at the RW 08 Community Hall, structured into four sequential sessions (visual education, CTPS and toothbrushing simulation, group health quiz, and creative drawing). A total of 22 children aged 6–12 years were selected via purposive sampling. Quantitative evaluation was performed using repeated measurements (Pre-Test to Post-Test Session 4) adapted from the Indonesian Ministry of Health guidelines and analysed using the Wilcoxon Signed-Rank Test. Qualitative findings were gathered through observational performance checklists. The GEMBIRA program was successfully executed with a 100% attendance rate. Inferential analysis demonstrated statistically significant improvements (p<0.05) across all evaluated indicators: diarrhea knowledge (p=0.001), toothbrushing knowledge (p=0.002), healthy snack consumption habits (p=0.001), and handwashing with soap/CTPS behaviour (p=0.003). Qualitatively, participants demonstrated spontaneous independence by correctly performing the 6-step CTPS technique prior to sessions without prompting. The GEMBIRA program is proven effective as a community-based educational intervention model to enhance cognitive capacity and promote healthy habituation among school-aged children. Participating children have the potential to act as peer-educators within their environment. It is recommended that local health cadres, schools, and primary health centers (Puskesmas) conduct routine monitoring and provide supporting sanitation facilities to ensure the long-term sustainability of healthy behaviours.